Association of neurodegeneration, cognitive impairment, and short stature in Down syndrome; Could proinflammatory cytokines be the common factor? - Ghazaleh Sadeghi; Mohammad Hadi Farjoo (Brain Research Bulletin)
Down syndrome (DS), caused by an extra copy of chromosome 21, is the most prevalent chromosomal disorder. It leads to various complications including, cardiac and endocrine dysfunctions, impairment of the immune system, growth retardation, and certain neurological conditions. Stunted growth in this population might be linked to an increased risk of a variety of co-occurring conditions, particularly neurological disorders. Studies indicate that the levels of neurodegeneration and neuroinflammation markers are higher in shorter children with DS. The disruption of insulin-like growth factor 1 (IGF1) signalling pathway due to the overexpression of proinflammatory cytokine genes could help establish a connection between short stature and neurodegeneration in DS. These cytokines disrupt the production of IGF1 in the liver, thereby inhibiting IGF1 from promoting bone and brain growth. Additionally, elevated cytokines levels impair the production of sex hormones by affecting the gonadal axis, further exacerbating the aforementioned conditions. The group of GnRH neurons responsible for cognitive functions is also impaired in DS, and treatment with GnRH agonists has demonstrated improvements in cognition. Although GnRH agonists can delay the fusion of growth plates by inhibiting pulsatile GnRH secretion, they may also lead to cognitive impairments. Hypothyroidism, the most prevalent endocrine complication of DS, can also contribute to both cognitive impairment and short stature. In conclusion, the increase of proinflammatory cytokines, through various mechanisms, can play a significant role in the development of both cognitive impairments and short stature in DS.